Zika Infection Disrupts Proteins Involved in the Neurosensory System - Glover, Kathleen K. M.; Zahedi-Amiri, Ali; Lao, Ying; Spicer, Victor; Klonisch, Thomas; Coombs, Kevin M. (Frontiers in Cell and Developmental Biology, 2020)
Newly re-emerging viruses are of great global concern, especially when there are no therapeutic interventions during the time of an outbreak. There are still no therapeutic interventions for prevention of Zika virus (ZIKV) infections despite its resurgence more than a decade ago. In addition to microcephaly, babies infected with ZIKV at birth face developmental challenges as they grow. These challenges are attributed to ZIKV infections causing delayed neuro development. Early identification and management of these developmental issues may improve quality of life for these children as they mature. Since all viruses hijack host cellular machinery to undergo successful replication, we applied tandem mass tag mass spectrometry-based proteomics to analyse changes within the cellular proteome during a time course. Among the thousands of host proteins dysregulated after ZIKV infection, bioinformatics predicted many linked to various neurodevelopmental processes, such as development of the auditory and retinal system, which are essential for hearing and vision. Further studies need to be done to determine how these dysregulated neurodevelopmental-associated host proteins are used by ZIKV during infection. This will hopefully identify key host proteins whose dysregulation results in various neurosensory alterations reported in children born to ZIKV infected mothers.